The Implementasi Metode On-Page Search Engine Optimization untuk Meningkatkan Peringkat Website sebagai Hasil Pencarian Google - Antonius Antonius; Bernard Renaldy Suteja (Maranatha University Press, 2021)
Current development of the internet world has been growing rapidly, especially in the field of website. People use search engines to find the news or information they needed on a website. One of the many indications of the success of a website is traffic. Traffic could be received from various factors, one of which is website rank in Search Engine Result Page (SERP). To improve the SERP, SEO methods are required. This research will implement SEO to website especially on the image, and then analyzed by using a tester tools, for example SEOptimer, Pingdom Tools, and SEO Site Checkup. After the website has been optimized, tested with the same tester tools. From the research results can be seen whether image optimization can affect SERP.